1997
DOI: 10.1021/es970032v
|View full text |Cite
|
Sign up to set email alerts
|

Butyltin Residues in Deep-Sea Organisms Collected from Suruga Bay, Japan

Abstract: Aquatic pollution resulting from extensive usage of organotin compounds has been of great concern due to their deleterious effects in organisms. However, organotin contamination in deep-sea ecosystems has not yet been studied. The present study was attempted to determine butyltin compounds (BTs), including mono-(MBT), di-(DBT), and tributyltin (TBT) in deep-sea organisms collected from Suruga Bay, Japan, in order to elucidate the contamination status and accumulation characteristics. The organisms were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 50 publications
7
36
0
Order By: Relevance
“…If BMF > 1, then the equilibrium whole-body-averaged concentration of the chemical will be higher in the predator than in its food. To calculate the BMF of TBT and MeHg for the American plaice, we used our experimental data (Table 1) and values of k, for MeHg in flatfish given by Jarvenpaa et al (1970) and Pentreath (1976) which comprised between 0.001 and 0.004 d-l. BA4Fcalculated this way ranges from 0.1 to 0.5 for TBT and from 2 to 9 for MeHg, values similar to those previously reported from the ratio of organometal concentration in various marine fish species over that measured in their food (Francesconi & Lenanton 1992, Takahashi et al 1997.…”
Section: Eliminationsupporting
confidence: 78%
See 1 more Smart Citation
“…If BMF > 1, then the equilibrium whole-body-averaged concentration of the chemical will be higher in the predator than in its food. To calculate the BMF of TBT and MeHg for the American plaice, we used our experimental data (Table 1) and values of k, for MeHg in flatfish given by Jarvenpaa et al (1970) and Pentreath (1976) which comprised between 0.001 and 0.004 d-l. BA4Fcalculated this way ranges from 0.1 to 0.5 for TBT and from 2 to 9 for MeHg, values similar to those previously reported from the ratio of organometal concentration in various marine fish species over that measured in their food (Francesconi & Lenanton 1992, Takahashi et al 1997.…”
Section: Eliminationsupporting
confidence: 78%
“…The fact that TBT is readily metabolised in organisms like fish and crustaceans suggests that the long-term biomagnification of TBT is not as significant as for MeHg and organochIorine pollutants (Fent 1996). However, recent monitoring results showed that TBT may be biomagnified by various marine organisms (Takahashi et al 1997, and references therein), indicating that the trophic transfer of this organometal needs to be investigated in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Organotin compounds, unlike other pollutants, are biodegradable and have a low assimilative nature, and thus are not easily transferred through trophic chains. Takahashi et al (1997; found no correlation between organotin concentrations and the place of the species in the trophic chain either.…”
Section: Introductionmentioning
confidence: 73%
“…Various marine organisms are affected by organotin compounds, mainly because of their bioaccumulative, deleterious effects (Takahashi et al, 1997). TBT has chronic toxic effects at very low concentrations (1 to 3 ng/L) (Takahashi et al, op.…”
Section: Introductionmentioning
confidence: 99%
“…4 The relative persistence of TBT in sediments makes it available to benthic biota. In fact, Takahashi et al 8 reported high levels of BT compounds in marine organisms collected at depths of 135-980 m in Suruga Bay (Japan).…”
mentioning
confidence: 99%